1999
DOI: 10.1002/(sici)1098-2795(199908)53:4<376::aid-mrd2>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor (VEGF) and its corresponding receptors (flt-1 and flk-1) in the bovine oviduct

Abstract: Vascular endothelial growth factor (VEGF) functions as a potent angiogenic protein as well as in regulating permeability. Reverse transcription‐polymerase chain reaction (RT‐PCR) and ribonuclease protection assay (RPA) were used to show that the bovine oviduct expresses VEGF and its two receptors flk‐1 and flt‐1. Expression of VEGF was relatively stable during the estrous cycle. In contrast, both receptor transcripts showed cycle‐dependent variations with significantly increased flt‐1 mRNA amounts before ovula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
36
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 35 publications
5
36
1
1
Order By: Relevance
“…The concentration of VEGF has been shown to range from 1 to 3 ng/ml and from 3 to 20 ng/g in cyclic bovine oviductal flushings and corpus luteum tissues, respectively [8,40]. Although the concentrations of VEGF used for treatment of the endometrial epithelial and stromal cells were higher than that of circulating levels (about 1.6 ng/ml) [41], the local concentration of VEGF in VEGF-producing tissues might be much higher than in plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of VEGF has been shown to range from 1 to 3 ng/ml and from 3 to 20 ng/g in cyclic bovine oviductal flushings and corpus luteum tissues, respectively [8,40]. Although the concentrations of VEGF used for treatment of the endometrial epithelial and stromal cells were higher than that of circulating levels (about 1.6 ng/ml) [41], the local concentration of VEGF in VEGF-producing tissues might be much higher than in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…The above findings suggest that VEGF has pivotal roles in regulating the functions of the cyclic and pregnant endometrium. In cows, VEGF expression has been observed in the ovary [7,8] and oviducts [9] throughout the estrous cycle and in the corpus luteum [8], placenta [10] and endometrium [10] during pregnancy. However, the expressions and functions of VEGF in the bovine endometrium during the estrous cycle have not yet been clarified.…”
mentioning
confidence: 99%
“…The local content of VEGF in the bovine oviduct is at its highest during the periovulatory period [8], and may be responsible for the higher fluid secretion within the oviduct during this period [24]. Moreover, we recently reported that VEGF may contribute to regulation of the different contractile patterns of the oviduct, which occur during the period of gamete and embryo transport [15].…”
Section: Discussionmentioning
confidence: 99%
“…I n t h e f e m a l e r e p r o d u c t i v e s y s t e m , t h e appropriate biological activity of VEGF and TNFα are crucial for the cascade of events that produce a successful pregnancy [8,13,15,[21][22][23]. The local content of VEGF in the bovine oviduct is at its highest during the periovulatory period [8], and may be responsible for the higher fluid secretion within the oviduct during this period [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation